Accounting, representation and responsibility : Deleuze and Guattari perspectives - Lennon, Niels Joseph (London : Routledge, 2021)
"In organizations, accounting produces organizational knowledge that affect decision making and managerial action. Companies placing importance on shareholder value sometimes tend to elevate accounting to a higher truth criterion for justifying managerial actions. Yet, the nature of accounting renders it difficult to argue that accounting information necessarily produce a better basis for decision making than arguments which are not based on accounting. This is because, as previous research has also argued, accounting counts some things but omits many others, while managers are accountable for much more than what accounting actually counts. Using a theoretical apparatus from Deleuze & Guattari, this book illustrates that accounting-based actions such as making management decisions, maintaining organisational responsibility and hierarchical control, are manifestations of the ways in which accounting is composed. This concise introduction will be invaluable for researchers and advanced students of management accounting exploring responsibility accounting and accountability"--
Part I: Theoretical Plateaus -- Introduction -- What can Accounting Learn from Deleuze? -- Is Accounting Representation Work or Visualization (Re-presentation) Work? -- What is Accountability? Accountability, Responsibility and Responsibility Accounting -- Part II: Empirical Plateaus -- Territorializing Accountability -- Deterritorializing Accountability
Includes bibliographical references and index.
Keywords: Accounting -- Philosophy; Decision making; Responsibility accounting; Managerial accounting